CKD patients comorbid with hypertension are associated with imbalanced gut microbiome - Pan Wang; Yang Shen; Kaixin Yan; Siyuan Wang; Jie Jiao; Hongjie Chi; Jiuchang Zhong; Qianmei Sun; Ying Dong; Jing Li (iScience)
Summary: Intestinal flora has been linked to chronic kidney disease (CKD) and hypertension, respectively. This study aimed to investigate the microbial community among 54 individuals without CKD, 46 hypertensive CKD patients (CKD_HTN), and 48 non-hypertensive CKD patients. Variations in microbial diversity were detected in CKD. The Prevotella-dominated type progressively increased from CKD to CKD_HTN. Based on the variation patterns, we identified six distinct clusters. Klebsiella, Turicibacter, and Enterobacter were enriched in CKD, whereas Escherichia and Mogibacterium were elevated, and Blautia and Clostridium were reduced in CKD_HTN. Enhanced phenylalanine metabolism and siderophore group nonribosomal peptides biosynthesis from non-CKD to CKD were observed, particularly in CKD with hypertension. The connections between genera and KEGG pathways suggest an impact of microbial dysbiosis on metabolism. Our findings demonstrate that imbalances in gut microorganisms and functions are associated with increased susceptibility to hypertension in CKD patients and could be targeted for improving kidney function in CKD.